Experience of nurses in the process of donation of organs and tissues for transplant - Edvaldo Leal de Moraes; Marcelo José dos Santos; Miriam Aparecida Barbosa Merighi; Maria Cristina Komatsu Braga Massarollo (Universidade de São Paulo, 2014)
OBJECTIVE: to investigate the meaning of the action of nurses in the donation process to maintain the viability of organs and tissues for transplantation.METHOD: this qualitative study with a social phenomenological approach was conducted through individual interviews with ten nurses of three Organ and Tissue Procurement Services of the city of São Paulo.RESULTS: the experience of the nurses in the donation process was represented by the categories: obstacles experienced in the donation process, and interventions performed. The meaning of the action to maintain the viability of organs and tissues for transplantation was described by the categories: to change paradigms, to humanize the donation process, to expand the donation, and to save lives.FINAL CONSIDERATIONS: knowledge of the experience of the nurses in this process is important for healthcare professionals who work in different realities, indicating strategies to optimize the procurement of organs and tissues for transplantation.